Writing prejudices : the psychoanalysis and pedagogy of discrimination from Shakespeare to Toni Morrison - Samuels, Robert, 1961- (Albany : State University of New York Press, 2001)
"Writing Prejudices addresses critical attempts to undermine prejudice through education in general, and literary studies in particular. Robert Samuels argues that these attempts often fail because they do not take into account the different forms of prejudice, the role played by homophobia in racism and sexism, the structure of what Lacan calls symbolic castration, and the unconscious foundations of cultural formations. Addressing these deficiencies, Samuels uses psychoanalytic theory to examine the manifestations of racism, sexism, ethnocentrism, and homophobia in the works of Shakespeare, Mary Shelley, Joseph Conard, and Toni Morrison, showing how these distinct modes of oppression feed off of each other and the diverse ways that cultural critics can work to undermine them."--Jacket
Part One. Early modern prejudice -- Introduction -- Racism, sexism, and homophobia in Othello -- The cycle of prejudice in Shakespeare's miscegenating Sonnets -- The Tempest: colonial desire, homophobic racism, and the ideological structures of prejudice -- Part Two. Colonialism, slavery, and racist homophobia -- Frankenstein's homosocial colonial desire -- The heart of darkness and homophobic colonial desire -- Part Three. Postmodern prejudice -- Internalized racism and the structures of prejudice in The bluest eye -- Beloved: psychoanalytic cultural criticism and the national unconscious -- Conclusion.
Includes bibliographical references (pages 183-189) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Morrison, Toni -- Criticism and interpretation; Morrison, Toni; English literature -- History and criticism -- Theory, etc; Psychoanalysis and literature -- England; Psychoanalysis and literature -- United States; Homophobia in literature; Racism in literature; Prejudices in literature; Discrimination in literature; Psychanalyse et littérature -- Angleterre; Psychanalyse et littérature -- États-Unis.; Racisme dans la littérature.; Préjugés dans la littérature.; Homophobie dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Discrimination in literature; English literature -- Theory, etc; Homophobia in literature; Prejudices in literature; Psychoanalysis and literature; Racism in literature; England; United States; Criticism, interpretation, etc